(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2025)
Chronic kidney disease (CKD) is a progressive condition characterized by declining kidney function, often coexisting with hypertension, type 2 diabetes mellitus (T2DM), and coronary artery disease (CAD), amplifying cardiovascular risks. Vrikka Vikar often manifests as a result of Prameha and Raktagata Vata, which collectively aggravate Hridroga, forming a complex pathophysiological interplay requiring a holistic Ayurvedic approach involving Shodhana and Shamana therapies. This case report presents a 52-year-old male with CKD, hypertension, T2DM, and CAD who underwent Ayurvedic interventions alongside conventional treatments at Jeena Sikho Lifecare Limited Hospital, Derabassi, Punjab, India. The patient experienced symptoms such as weakness, fatigue, frothy urine, disturbed sleep, and lower back pain. Following a 13-day inpatient Ayurvedic treatment regimen, the patient’s symptoms improved significantly. Laboratory investigations revealed a reduction in serum urea from 137.17 mg/dL to 75.44 mg/dL, serum creatinine from 6.88 mg/dL to 5.58 mg/dL, and uric acid from 7.30 mg/dL to 6.44 mg/dL. These outcomes suggest that Ayurvedic interventions may support improved kidney function and overall well-being. Further controlled studies are recommended to validate these findings and develop standardized treatment protocols.